Dietary patterns and respiratory health in adults from nine European countries – evidence from the GA2LEN study - Bakolis,I; Hooper,R; Bachert,C; Lange,B; Haahtela,T; Keil,T; Hofmaier,S; Fokkens,W; Rymarczyk,B; Janson,C; Burney,PG; Garcia,Larsen V (Clinical and Experimental Allergy, 2018)
Background: Dietary patterns defined using Principal Component Analysis (PCA) offer an alternative to the analysis of individual foods and nutrients and have been linked with asthma and allergic disease. However, results have not been reproducible in different settings.Objective: To identify dietary patterns common to different European countries and examine their associations with asthma and allergic symptoms. Methods: In sixteen study centres in nine European countries, 3206 individuals aged 15-77 years completed a common, internationally validated, Food Frequency Questionnaire and a respiratory symptoms questionnaire. The outcomes of interest were current asthma, asthma symptoms score (derived based on responses to 5 asthma symptom-related questions), atopy (positive skin prick test). Spirometry was used to estimate forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), the FEV1/FVC, spirometric restriction (FVC below the lower limit of normal (<LLN)) and FEV1/FVC < LLN. A novel meta-analytic approach was used to identify dietary patterns using PCA and to examine associations with asthma and allergic symptoms.Results: Two dietary patterns emerged, generally correlating with the same foods in different countries: one associated with intake of animal proteins and carbohydrates; the other with fruit and vegetables. There was evidence that the former pattern was associated with a higher asthma score (RR 1.63, 95% CI: 1.33-2.01), current asthma (RR 2.03, 95% CI: 1.52-2.71), wheeze (RR 1.84, 95%CI: 1.30-2.60), atopic status (RR 1.68, 95%CI: 1.16-2.44) and with decreased lung function, including an FVC <LLN (RR 4.57, 95% CI: 2.27-9.21). Conclusions & Clinical Relevance: Our findings suggest an increase in sensitisation to common allergens, an increase in asthma symptoms and a reduction in lung function in those eating a diet rich in animal proteins and carbohydrates. We found little evidence of an association between these outcomes and